Understanding your health - Payne, Wayne A (McGraw-Hill, 2009)
This text offers an exciting and practical approach to the teaching of the traditional content areas of personal health. Its two key themes--the six dimensions of health and the five developmental tasks--help students apply the text's content to their own lives by improving their decision-making skills. The companion Online Learning Center offers a wealth of pedagogical and assessment features, including quizzes, links, study aids, and more.